Estimation of Temperature over Nepal - Nayava, Janak Lal (Himalayan Review, 2011)
Not available. Key words: Temperature; Plant growth; Agriculture planning; Nepal The Himalayan Review Vol. 14, 1982 Page: 12-24 Uploaded Date: April 10, 2011